PERAN PEREMPUAN REMAJA DAN KELUARGA DALAM KETAHANAN KELUARGA PERSPEKTIF HUKUM ISLAM - Musyahidah, Sitti (Pusat Studi Gender dan Anak, IAIN Palu, 2019)
Women and teenagers will not be separated from one another. Since Kartini fought for the position of women equal to men. Much further, the Qur'an came to give a very noble position for women proved that the existence of Surah an-Nisa means woman. Therefore, the position of women and even teenagers also contribute to a set of challenges faced by every teenager. Teenagers are ideal when faced with a social, moral, economic problem. Considering that adolescents still have a very weak absorptive capacity in the form of equality in any case, so the role of adolescents is a benchmark in the challenges of globalization.